2011
DOI: 10.1111/j.1708-8208.2011.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Immediate Loading of Electroeroded Screw‐Retained Titanium Fixed Prostheses Supported by Tilted Implant: A Multicenter Retrospective Study

Abstract: Statement of problem: Immediate occlusal loading of dental implants in the edentulous mandible has proven to be an effective, reliable, and predictable treatment protocol. However, there is limited long-term data available in the literature, when an electroeroded definitive cast-titanium fixed prosthesis is used for this treatment protocol.Purpose: The aim of this study was to evaluate the clinical effectiveness of dental implants (Astra Tech Dental, Mölndal, Sweden) in the edentulous mandible immediately load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
0
12
0
4
Order By: Relevance
“…Twenty-five prospective studies 8,13-36 and nineteen retrospective analyses 1,3,7,37-52 were included in the meta-analysis. Five studies 15,18,20,27,44 were multicenter. Four studies 24,31,39,40 had a relatively short follow-up time (up to 12 months).…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty-five prospective studies 8,13-36 and nineteen retrospective analyses 1,3,7,37-52 were included in the meta-analysis. Five studies 15,18,20,27,44 were multicenter. Four studies 24,31,39,40 had a relatively short follow-up time (up to 12 months).…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…Some patients in thirty-three studies 1, 3,7,8,14,15,17,18,[20][21][22][23][24][25][27][28][29][30][32][33][34]36,[40][41][42][44][45][46][47][48][49]51,52 were smokers. Five studies 16,42,44,46,49 reported the presence of bruxers among the patients, and six studies 1, 28,42,46,48,49 the presence of diabetic patients. In twelve studies [17][18][19]21,22,27,32,34,36,…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations